OF TECHNOLOGY, YEATS AND AUTOMATIC WRITING: MANAGING CULTURAL IDENTITIES IN THE AGE OF AI ETHICS AND BEYOND. - Štefl, Martin (Litteraria Pragensia: Studies in Literature & Culture, 2025)
Pondering about the esoteric system of A Vision, the result of countless revisions of a suspicious, yet irresistibly seductive automatic text, Yeats, half despairing, half enthralled, finally concludes that the whole experience affirms "that all the gains of man come from conflict with the opposite of his true being." The opaqueness and blackbox-like quality of automatic writing, eerily akin to the experience of eliciting a meaningful AI-generated answer, reminds today's readers of the importance of a question-answer/prompt-response dialectic, so often neglected (especially by students) when faced with the seeming flawlessness and artifice of an AI-generated text. The responsibility to creatively engage with an otherwise ossified text further points towards a similar line of criticism aimed at various reifications and reductions of culture, which, in effect, mask the dynamic, performative character of cultural identities, e.g., by bracketing out an individual's creativity and responsibility when applying a positivistic, data-based cultural model. Departing from Yeats, a poet of multiple cultural allegiances, AI ethics, and philosophy of technology, this article aims to explore the mutually overlapping yet ever-conflicting ways in which cultural identities are produced in current intercultural theories, hoping to deconstruct currently dominant static models of culture in favour of a dynamic, critical approach to (re-)presenting cultures.